2011
DOI: 10.1002/cncr.26069
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Epstein‐Barr virus DNA screening followed by 18F‐fluoro‐2‐deoxy‐D‐glucose positron emission tomography in detecting posttreatment failures of nasopharyngeal carcinoma

Abstract: BACKGROUND:The authors investigated the clinical implication of plasma Epstein‐Barr virus (EBV) DNA assay and 18F‐fluoro‐2‐deoxy‐D‐glucose (18F‐FDG) positron emission tomography (PET) in the detection of recurrent nasopharyngeal carcinoma (NPC).METHODS:Two hundred forty‐five patients with NPC who had previously received treatment and were in a state of remission were monitored prospectively using a plasma EBV DNA assay every 3 to 6 months. 18F‐FDG PET studies were obtained when abnormal EBV DNA or clinically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 17 publications
1
47
0
1
Order By: Relevance
“…Notably, Ma et al have recently reported that the level of circulating EBV DNA was significantly associated with NPC tumor volume as assessed by MRI as well as SUV of the primary tumor and the metastatic lymph nodes (23), but they did not demonstrate the measurement of other 18 F-FDG PET functional parameters. Wang et al addressed the potential utility of posttreated plasma EBV DNA and 18 F-FDG PET in detecting tumor relapse after treatment, but they did not evaluate any pretreated measurement of EBV DNA load and 18 F-FDG PET as described in the current study (34).…”
Section: Discussionmentioning
confidence: 97%
“…Notably, Ma et al have recently reported that the level of circulating EBV DNA was significantly associated with NPC tumor volume as assessed by MRI as well as SUV of the primary tumor and the metastatic lymph nodes (23), but they did not demonstrate the measurement of other 18 F-FDG PET functional parameters. Wang et al addressed the potential utility of posttreated plasma EBV DNA and 18 F-FDG PET in detecting tumor relapse after treatment, but they did not evaluate any pretreated measurement of EBV DNA load and 18 F-FDG PET as described in the current study (34).…”
Section: Discussionmentioning
confidence: 97%
“…It was suggested that high circulating plasma EBV DNA load assessed 6 weeks post-primary treatment may predict a subsequent relapse [27][28][29]. For patients treated due to NPC persisting, increased, post-treatment viral DNA load or a subsequent rise after a previous drop seems to be an indication for PET/CT scanning for high risk of relapse [30]. Campitelli et al showed an analysis of sequential serum specimens in patients with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PET/CT parameters other than SUV max have been received more and more attentions in the prognosis of solid cancers [64][65][66][67][68][69]. SUV max is a semiquantitative index and can be is theoretically a better predictor of outcome than SUV max [65].…”
Section: Therapeutic Response Assessmentmentioning
confidence: 99%
“…Total lesion glycolysis represents metabolic activity throughout the entire tumor above a minimum threshold [69], might reflect the metabolic burden better than SUV max . In a study [60] Mä kitie et al [68] performed the first study combing EBV DNA copies and 18 F-FDG PET/CT in response evaluation and prognosis prediction.…”
Section: Therapeutic Response Assessmentmentioning
confidence: 99%
See 1 more Smart Citation